Thymic Microenvironment Remodeling in Cancer Cachexia as a Determinant of Checkpoint Inhibitor Efficacy and Toxicity - Run‐Kai Huang; Yan‐Fang Xing; Xiang‐Yuan Wu; Zhao‐Hui Shi; Li Wei; Xiao‐Tong Lv; Lin‐Jiao Peng; Xiu‐Qing Pang; Qin‐Tai Yang; Xing Li (Journal of Cachexia, Sarcopenia and Muscle)
ABSTRACT Background The discovery of immune checkpoints links autoimmunity and cancer, with thymus atrophy reportedly causing autoimmune multiorgan inflammation. The impact of cancer cachexia on thymic involution and its clinical significance remains unclear. This study aimed to investigate this effect and its association with immune checkpoint inhibitor (ICI) treatment. Methods Single‐cell sequencing, immunofluorescence and flow cytometry analyses were conducted to explore changes in the thymus in orthotopic hepatocellular cancer (HCC) mice with cachexia. Patients with advanced and locally advanced cancers receiving anti‐PD‐1/L1 antibody treatment were followed up to investigate the relationship between the amount of serum autoantibodies and the efficacy of ICIs. Results Single‐cell sequencing in cachexic HCC mice revealed thymic fibroblast maturity disorders characterized by elevated immature medullary fibroblasts, impaired antigen processing functions, reduced interaction with single‐positive thymocytes and decreased expression of tissue‐restricted antigen‐related genes. The thymus of mice with cancer cachexia exhibited degradation of the thymic medulla and decreased expression of LtβR, Mmp9 and Ccl19 in thymus medullary fibroblasts (mFbs). Single‐cell TCR sequencing showed that inflammatory‐related V/J TCR genes were highly used in expanded thymocyte clonotypes in cachexic HCC mice, suggesting impaired T cell negative selection. Results from coculture and cell transfer assays suggest that cancer cachexic CD45+ erythroid progenitor cells (EPCs) induce the death of CD34+ progenitor cells and decrease the number of LtβR+, Mmp9+ and Ccl19+ mFbs in tumour‐free mice. CD24+CD4+CD8− single‐positive thymocytes, typically eliminated in negative selection, did not decrease after the administration of anti‐CD3 mAb. Serum autoantibodies were markedly produced in cachexic HCC mice, cachexic HCC mice administered with anti‐PD1 and tumour‐free mice that received cancer cachexic CD45+ EPCs. Autoantibodies against tumour‐restricted antigens were found in patients with advanced and locally advanced cancer who received two cycles of ICI treatment. Univariate Cox regression analysis showed that patients with a low level of autoantibodies had a higher risk of disease progression (hazard ratio [HR]: 2.39, 95% CI [1.02–5.63], p = 0.046). Analysis of the receiver operating characteristic curve indicated that the number of autoantibodies against tumour tissues predicted treatment failure (area under the curve [AUC] 0.726, p = 0.021) and long‐term duration of treatment response (AUC 0.697, p = 0.024). Patients with high levels of serum autoantibodies against tumours had favourable progression‐free survival (HR, 0.389; 95% CI [0.158–0.960], p = 0.04). Conclusions Cancer cachexia disrupts mFbs maturity, affecting T cell negative selection and expanding the TCR repertoire against tissue‐restricted antigens. This might mediate the adverse and favourable effects of ICIs as anticancer treatments.